DNA-based diet analysis of mesopelagic fish from the southern Kerguelen Axis. (April 2020) - Clarke, Laurence J.; Trebilco, Rowan; Walters, Andrea; Polanowski, Andrea M.; Deagle, Bruce E.
Abstract: Mesopelagic fish form an important link between zooplankton and higher trophic levels in Southern Ocean food webs, however their diets are poorly known. Most of the dietary information available comes from morphological analysis of stomach contents and to a lesser extent fatty acid and stable isotopes. DNA sequencing could substantially improve our knowledge of mesopelagic fish diets, but has not previously been applied. We used high-throughput DNA sequencing (HTS) of the 18S ribosomal DNA and mitochondrial cytochrome oxidase I (COI) to characterise stomach contents of four myctophid and one bathylagid species collected at the southern extension of the Kerguelen Plateau (southern Kerguelen Axis), one of the most productive regions in the Indian sector of the Southern Ocean. Diets of the four myctophid species were dominated by amphipods, euphausiids and copepods, whereas radiolarians and siphonophores contributed a much greater proportion of HTS reads for Bathylagus sp. Analysis of mitochondrial COI showed that all species preyed on Thysanoessa macrura, but Euphausia superba was only detected in the stomach contents of myctophids. Size-based shifts in diet were apparent, with larger individuals of both bathylagid and myctophid species more likely to consume euphausiids, but we found little evidence for regional differences in diet composition for each species over the survey area. The presence of DNA from coelenterates and other gelatinous prey in the stomach contents of all five species suggests the importance of these taxa in the diet of Southern Ocean mesopelagics has been underestimated to date. Our study demonstrates the use of DNA-based diet assessment to determine the role of mesopelagic fish and their trophic position in the Southern Ocean and inform the development of ecosystem models.